2021
DOI: 10.1098/rsta.2021.0108
|View full text |Cite|
|
Sign up to set email alerts
|

Is the destruction or removal of atmospheric methane a worthwhile option?

Abstract: Removing methane from the air is possible, but do the costs outweigh the benefits? This note explores the question of whether removing methane from the atmosphere is justifiable. Destruction of methane by oxidation to CO 2 eliminates 97% of the warming impact on a 100-yr time scale. Methane can be oxidized by a variety of methods including thermal or ultraviolet photocatalysis and various processes of physical, chemical or biological oxidizers. Each removal method has energy costs (with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…To address these more diffuse sources and reduce atmospheric methane concentrations, some researchers have argued for removing atmospheric methane via oxidation, the process that converts methane into carbon dioxide and water. Various research groups have outlined the associated opportunities, challenges, and research directions to better understand the technical and economic feasibility of methane oxidation [6][7][8][9][10]. Methane can also be oxidized at its emission sources where its concentration is higher than atmospheric levels.…”
Section: Introductionmentioning
confidence: 99%
“…To address these more diffuse sources and reduce atmospheric methane concentrations, some researchers have argued for removing atmospheric methane via oxidation, the process that converts methane into carbon dioxide and water. Various research groups have outlined the associated opportunities, challenges, and research directions to better understand the technical and economic feasibility of methane oxidation [6][7][8][9][10]. Methane can also be oxidized at its emission sources where its concentration is higher than atmospheric levels.…”
Section: Introductionmentioning
confidence: 99%
“…Jackson et al 5 claimed the GWP of the CH 4 was 84 times that of CO 2 in the first 20 years after it was produced, and it was still 28 times that of CO 2 in the next 100 years. As a result, the total oxidation of atmospheric CH 4 to CO 2 removes 97% of the warming effect over a century time period, leading to significant climatic benefits 5‐7 . Recently, several strategies for removing atmospheric CH 4 were described and compared in detail 8 …”
Section: Introductionmentioning
confidence: 99%
“…As a result, the total oxidation of atmospheric CH 4 to CO 2 removes 97% of the warming effect over a century time period, leading to significant climatic benefits. [5][6][7] Recently, several strategies for removing atmospheric CH 4 were described and compared in detail. 8 Photocatalysis technology offered a promising way to remove the methane in the atmosphere.…”
mentioning
confidence: 99%
“…Converting methane to methanol is another considerable way to reduce methane gas emission because of its significant cost advantages in transportation and storage. , Converting methane to methanol through partial oxidation at room temperature has remained a challenging issue in catalysis for decades. The CH 4 molecule has a tetrahedral shape, which confers stability and a nonpolar nature. The difficulty arises not only from the strong bonding energy of the C­(sp 3 )–H bond (439 kJ mol –1 ) but also the overoxidation tendency, leading to the formation of CO 2 . Mounting research has suggested H 2 O 2 as an excellent oxidant for converting methane to methanol because of its green oxidation byproduct (water). …”
mentioning
confidence: 99%
“…Unfortunately, there is no effective method to remove methane from the air. Oxidation of methane to CO 2 is one of solutions that could reduce methane’s 20-year global warming impact by 99%. , Catalytic combustion requires a temperature of higher than 400 °C to convert CH 4 to CO 2 at 90% efficiency, making it a highly energy-intensive process . There is often severe performance degradation under such hydrothermal conditions, making high-temperature catalytic combustion for dilute and atmospheric methane removal unviable.…”
mentioning
confidence: 99%